2020
DOI: 10.1021/acsomega.0c05236
|View full text |Cite
|
Sign up to set email alerts
|

Study for the Effect of Temperature on Methane Desorption Based on Thermodynamics and Kinetics

Abstract: Desorption hysteresis is important for primary gas production. Temperature may cause serious changes in the methane adsorption/ desorption behaviors. In order to study the mechanism of methane desorption and desorption hysteresis, three sets of samples of long-flame coal, coking coal, and anthracite were collected, and experiments such as microscopic composition determination, liquid nitrogen adsorption, and isothermal adsorption/desorption were performed. From the perspectives of desorption kinetics, desorpti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Through low-temperature N 2 adsorption (LTAN) and lowpressure CO 2 adsorption (LPCA) experiments, Hu et al (2020) and found that super micropore structures smaller than 2 nm accounted for the majority of the total pore specific surface, while methane adsorption capacity increased with the increase of micropore PV and micropore SSA, concluding that super micropore structures smaller than 2 nm were the dominant factor affecting methane adsorption capacity. The production of CBM mainly goes through the processes of drainage depressurization-desorption-diffusion-seepage (Lin et al, 2016;Gao et al, 2020). Maximizing the desorption of gas adsorbed inside the pore space is the most important factor in achieving maximum capacity in CBM wells.…”
Section: Introductionmentioning
confidence: 99%
“…Through low-temperature N 2 adsorption (LTAN) and lowpressure CO 2 adsorption (LPCA) experiments, Hu et al (2020) and found that super micropore structures smaller than 2 nm accounted for the majority of the total pore specific surface, while methane adsorption capacity increased with the increase of micropore PV and micropore SSA, concluding that super micropore structures smaller than 2 nm were the dominant factor affecting methane adsorption capacity. The production of CBM mainly goes through the processes of drainage depressurization-desorption-diffusion-seepage (Lin et al, 2016;Gao et al, 2020). Maximizing the desorption of gas adsorbed inside the pore space is the most important factor in achieving maximum capacity in CBM wells.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of gas content is firstly controlled by geological structure. Regional and mine structures form different sealing conditions, which have a considerable control effect on the distribution of gas content in coal seams (Moore 2012;Gao et al 2020;Quan et al 2020). Given a large compressive stress in compressional fault, fault gouge and mylonite with compacted structure are relatively developed, and the permeability of gas is poor (Bustin and Clarkson 1998;Zhang et al 2016;Tong et al 2019).…”
Section: Understanding Of Coal Seam Gas Occurrence Characteristicsmentioning
confidence: 99%
“…With an increase in the degree of metamorphism of coal, the diffusion coefficient of methane first decreases and then gradually increases. , Through analysis of the change laws of the Langmuir effective diffusion coefficient with the coal rank and their influencing factors, Yan found that a rise in the coal rank increased the development degree of micropores and gas desorption capacity. Wang, Gao, and Lin concluded a higher adsorption pressure of coal mass is related to the stronger movement of methane molecules, more favorable for gas desorption, and accelerates gas diffusion. Additionally, the high pressure increases the diffusion coefficient and the cumulative amount of gas desorption and diffusion.…”
Section: Introductionmentioning
confidence: 99%